Managing visitor attractions - Fyall, Alan; Leask, Anna; Wanhill, Stephen; Garrod, B. (Brian) (London New York Routledge, Taylor & Francis Group, 2022)
"Visitor attractions represent a complex sector of the tourism industry and are the catalytic focus for the development of tourism infrastructure and services. The third edition of this successful text investigates these issues further and provides more solutions and suggestions for the present and future. With contributions from around the world, this is an essential text for undergraduate and postgraduate students of visitor attraction management, written by subject specialists with a wealth of experience in this field"--
"First edition published by Routledge 2012. Second edition published by Routledge 2009" -- Title page verso.
Includes bibliographical references and index.
Keywords: Tourism -- Management; Tourism -- Marketing